α-Fe2O3 nanotubes-reduced graphene oxide composites as synergistic electrochemical capacitor materials - Lee, K. K. (2013)
We present a facile approach for the fabrication of a nanocomposite comprising α-Fe2O3 nanotubes (NTs) anchored on reduced graphene oxide (rGO) for electrochemical capacitors (ECs). The hollow tubular structure of the α-Fe2O3 NTs presents a high surface area for reaction, while the incorporation of rGO provides an efficient two-dimensional conductive pathway to allow fast, reversible redox reaction. As a result, the nanocomposite materials exhibit a specific capacitance which is remarkably higher ([similar]7 times) than α-Fe2O3 NTs alone. In addition, the nanocomposites show excellent cycling life and large negative potential window. These findings suggest that such nanocomposites are a promising candidate as negative electrodes in asymmetrical capacitors with neutral electrolytes.